Consumer Perceptions Of Price and Promotion On Airline Ticket Purchase Decisions at PT Pratama Mandiri Abadi - Rahmah Hamidah; annisa soraya; sari lestari zainal ridho; yusleli herawati (International Journal of Advanced Research in Social Studies, 2022)
This research was conducted to determine the company's ability to generate profits and to manage and allocate products through purchase decisions by analyzing consumer perceptions, price, and promotion at PT Pratama Mandiri, in order to identify which indicator has the most dominant influence on purchase decisions. The data collection techniques used in this research include observation, questionnaires, and interviews. The sampling technique applied was non-probability sampling using a purposive sampling method. The sample characteristics in this study were respondents who are currently purchasing or have previously purchased airline tickets at PT Pratama Mandiri. Data processing was carried out using quantitative analysis to calculate the number of respondents who answered the questionnaires. In the calculation, the researcher used percentage formulas and score interpretation. The price indicator had a score interpretation of 90%, the promotion indicator scored 86.8%, and the purchase decision indicator scored 88%. Among these three indicators, the purchase decision indicator received the highest score of 93.2%, indicating that it has the greatest influence compared to the other two indicators. The implementation of discounts during major holidays has proven effective in attracting consumer buying interest, thereby increasing the likelihood of consumers purchasing airline tickets at PT Pratama Mandiri. Keywords: Airline Tickets, Consumer Perception, Price, Promotion, Purchase Decision